Telaah Nilai-nilai Moderasi Beragama yang Terkandung Dalam Film Ayat-Ayat Cinta 2 - Muhamad Rouf Didi Sutriadi; M Jia Ulhaq (ISTIFHAM, 2023)
The film ayat-2 is a film that was translated from a novel by Habiburrahman El Shirazy with the same title. This research examined the values ​​of religious moderation contained in the film. The researcher observes and describes the film Ayat-ayat Cinta 2 to obtain a more comprehensive analysis. The researcher also uses the theory of religious moderation used by the Ministry of Religion to analyze the film. After that, the researcher mapped out several scenes containing religious moderation values. The results of this study researchers found four scenes that carry the value of religious moderation. First, the scene of Fahri helping Grandma Caterina by taking her to the place of worship of the Jews is included in the "principle of relations between religions." Second, the religious moderation book explains the value of "Searching for Common Points." This is similar to what is presented in the film Ayat-Ayat Cinta 2. Fahri explains that only love should be loved and only enmity should be despised. This sentence applies to all humans and even all religions. Third, in religious moderation, it is required that every religious community not close themselves off from other people with different beliefs. Instead, be open. Fahri's action to help Keira, a Jewish neighbor who hates Fahri, by giving free and selfless education or music lessons to Keira is a form of attitude approved by the religious moderation guidebook of the Indonesian Ministry of Religion, namely in the form of the value of "movement moderation." Fourth, the value of "advising others wisely" is evident in Fahri's attitude, even though he disagrees with Hulusi's opinion, he still gives a rebuttal in a gentle tone and does not feel high even though Hulusi is the driver.